RANCANG BANGUN SISTEM KONTROL DAN MONITORING KEAMANAN RUMAH DENGAN NODEMCU ESP32 BERBASIS IOT - Saefatu, Fredwin; Ir. Gigih priyandoko, MT. Ph.D; Dedi Usman Effendy, ST. MT (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2025)
In the modern era, the Internet of Things (IoT) technology has brought about a significant revolution in the technological landscape, particularly in the realm of home security [1]. As the incidents of home accidents such as gas leaks, smoke-related fires, and theft cases continue to rise [2], it becomes imperative to mitigate these risks through the development of IoT-based control and monitoring systems for home electronic security devices. This research designs and constructs an IoT-based home security system to address the aforementioned risks. The system employs various sensors including DHT11 (temperature), MQ-4 (smoke and gas), KY026 (flame), PIR (motion), and MC38 (door/window status), all interconnected with the NodeMCU ESP32 microcontroller. The outcomes from these sensors are displayed on an LCD I2C screen, the Blynk application, and also sent via email. Sensor integration triggers preventive actions, such as activating a fan when the temperature exceeds 27°C, initiating emergency lighting in case of gas levels surpassing 500, and activating a water pump when flames are detected. The PIR sensor connects to an ESP32 CAM that captures and emails images upon motion detection. Testing demonstrates the sensors' reliable reception of inputs and their high sensitivity, while the NodeMCU ESP32 microcontroller effectively transmits data to Blynk and email, controls electronic devices, and presents information on the LCD I2C screen. The Blynk application and email successfully receive data within varying ranges of 1m, 350m, 800m, 1.3km, and 2.7km. This research culminates in a functional prototype that successfully implements IoT concepts for real-time monitoring and control of home security devices. As such, this study offers a positive contribution towards raising awareness about home security and furnishes an intelligent solution for mitigating accident and theft risks.